COMENTARIOS A LOS CUATRO EVANGELIOS - Maldonado, Juan de (BIBLIOTECA DE AUTORES CRISTIANOS;, 1950)
CONTENIDO: V.1 EVANGELIO DE SAN MATEO.-- V.2 EVANGELIOS DESAN MARCOS Y SAN LUCAS.-- V.3 EVANGELIO DE SAN JUAN